The landscape catalog as a tool for consensus - Case of Villa de Merlo, San Luis, Argentina - Cresmani, Mónica Liliana; Ciccarone, María Inés; Bianchi, Erico; Silvestre, Luciana Sol; Resio, Ana Sofía; Aguilera Marturano, Leticia; Casaretto, Eleonora; Segura, Adriana Gabriela (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The "Landscape" can be understood as a visual and cultural perception changing over time and interdisciplinary, which requires professional transversality to analyze the transformations that occur in urban and territorial scales through urban planning, to achieve a sensitive territory with quality of life. The laws of nature and human action modify its forms and geographical structures through environmental and social actions, as well as from the different views that are perceived. Landscape should not be perceived with a protectionist and static approach, it is necessary to consider the projective action for the transformation of the landscape or the creation of a new one. The impact of human action on landscapes confirms the need to rethink the way in which the territory is managed. The climate emergency and the inequalities generated by globalization call for a systematic search for global commitments supported by local actions. The landscape catalog is a methodological opportunity for a contemporary vision of the territory. In this process, the landscape begins to be identified as a central axis for a new management of the territory, as an identity manifestation that does not exclude the link between the community and the space it inhabits. In other words, to move from a static-delimiting look, from a static set of objects, with a prefixed meaning to a dynamic-ordering one, with an awareness of values that are linked to the changing needs and demands that society attributes to its landscape, through a useful tool for the implementation of landscape policies by integrating landscape objectives in territorial strategies with the connivance and active participation of all social agents involved in the territory.